Forsaken Foregut: Case Report of Simultaneous Black Esophagus and Ischemic Cholangiopathy - Paul A. Cameron; Franzjosef Schweiger (Case Reports in Medicine)
Black esophagus or acute esophageal necrosis rarely occurs after severe hemodynamic compromise or low-flow states. Other contributing factors may include corrosive injury from gastric contents and diminished mucosal repair mechanisms. Ischemic cholangitis, another rare clinical entity, is also usually the result of a significant vascular and/or hypotensive insult to the biliary tree. We describe the first case of combined acute esophageal necrosis and ischemic cholangiopathy in a 62-year-old male who completely recovered from the esophageal injury but developed progressive liver failure from ischemic cholangiopathy.